Numerical modelling of shallow foundation on multi-layer soil with varying stiffness - Aneel Kumar,; Zaheer Almani,; Syed Raghib Ali Shah,; Muhammad Rehan Hakro, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The load-deformation observation under the footing is essential for foundation design. Either experimental methods or numerical modelling generally determines this phenomenon in engineering practices. This study determined the settlement of shallow foundations on Multi-layer soil profile numerically. The settlement behavior was investigated through numerical modelling with Plaxis 2D. This study site was Jamshoro region, located in province Sindh, Pakistan. From the geotechnical investigation, the soil of Jamshoro region consists of a combination of different soils, mainly shale and limestone. This type of soil shows common challenges for the serviceable and sustainable design and construction of structural foundations. The standard penetration test conducted accompanied by other geotechnical tests on shale and limestone to determine the input parameters for the model and observe the soil profile. The Mohr-Coloumb model used for shale and linear elastic for limestone. The settlement of the foundation is attended by varying the limestone layer’s depth. In this research, the settlement reduced under the footing by increasing the thickness of the limestone layer. The study observed that stiffness of lower layer significantly reduces the settlement of shallow foundation. Therefore, the effect of lower layer should be considered for the designing of foundation on multi-layered soil.